COVID-19 Case Fatality Rate and Detection Ability in Indonesia - Sipahutar, Tiopan; Eryando, Tris (UI Scholars Hub, 2020)
The world is currently experiencing a COVID-19 pandemic. More than 5 million people have been infected with COVID-19 and more than 300 thousand have died from this virus worldwide. In Indonesia, the number of infected people has reached more than twenty thousand people and more than one thousand people have died from this virus. During the COVID-19 pandemic, Case Fatality Rate (CFR) was a very important measure for many people because death is very important to each person, including questions of when and how death will occur and whether there is any way to delay it. However, caution is needed in calculating and displaying CFR. This paper will present the uses and the weaknesses of CFR in the context of the COVID-19 pandemic in Indonesia.